A retrospective analysis of retirement of football players in Portugal - Travassos, Bruno (2018)
The purpose of this study was to analyse the retirement of elite football players in Portugal. Specifically, the quality of retirement and the resources available were evaluated. To develop an understanding of the process of the sporting retirement of elite football players we used data from in-depth, semi-structured interviews with ninety professional players from the portuguese football national team. Most of the elite Portuguese footballers we investigated retired from sport between 36 and 40 years of age, their retirement had been involuntary and it had taken them less than a year to accept retirement. Most had only been educated to secondary level and had a strong athletic identity, no plans for their post-football career exist and relied on family as their main psychological support. None of the players had received support from a formal programme. Despite of the findings being consistent with previous research from other Southern European cultures, it seems that the athletic retirement of portuguese footballers has some particularities. Most portuguese footballers retired later and had longer playing careers than athletes in other countries. In addition, retirement was involuntary in most of cases, yet players reported that it took them a relatively short time to accept retirement.